2011
DOI: 10.1016/j.jstrokecerebrovasdis.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke Aphasia Recovery Assessed With Functional Magnetic Resonance Imaging and a Picture Identification Task

Abstract: Background-Stroke patients often display deficits in language function such as correctly naming objects. Our aim was to evaluate the reliability and the patterns of post-stroke language recovery using a picture identification task during fMRI at 4T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 56 publications
3
40
0
2
Order By: Relevance
“…Post-stroke neuroimaging studies that have evaluated recovery from aphasia in adults with unilateral lesions show evidence of cortical reorganization and migration of language functions to the non-dominant hemisphere after a dominant hemisphere insult [20,23,39]. Interestingly, one study that showed such a redistribution pattern using PET and fMRI language tasks also found negative association between increased non-dominant inferior frontal gyrus activation and recovery after an ischemic stroke [40].…”
Section: Discussionmentioning
confidence: 99%
“…Post-stroke neuroimaging studies that have evaluated recovery from aphasia in adults with unilateral lesions show evidence of cortical reorganization and migration of language functions to the non-dominant hemisphere after a dominant hemisphere insult [20,23,39]. Interestingly, one study that showed such a redistribution pattern using PET and fMRI language tasks also found negative association between increased non-dominant inferior frontal gyrus activation and recovery after an ischemic stroke [40].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies focused on the spontaneous recovery of language, [1][2][3][4][5][6][7] but only a few, often single case descriptions, focused on patients submitted to language rehabilitation. [8][9][10][11][12][13] All of these were conducted on chronic patients. The rate of complete spontaneous (ie, without language therapy) aphasia recovery poststroke has been estimated at ≈33% in the first month, 43% after 4 months, and 50% 12 months later.…”
mentioning
confidence: 99%
“…Aphasia may be one of the best-studied clinical conditions when it comes to the attempted mapping of the neural substrate of functional recovery. Aphasias primarily result from injury to the left hemisphere, and ipsilateral contributions to the mediation of reacquired linguistic functions have been documented by for instance Szaflarski et al (2011), Perani et al (2003), Specht et al (2009), andMeinzer et al (2008). Meinzer et al (2008) demonstrated treatment-induced reintegration of various perilesional areas.…”
mentioning
confidence: 99%